TCP/IP - Messier, Ric (Infinite Skills, 2013)
In this TCP/IP training course from author and expert trainer Ric Messier, you will learn all about the standard communication protocol for the internet. TCP/IP (Transmission Control Protocol / Internet Protocol) defines how devices connect to, and communicate through the internet. This tutorial explains how TCP/IP packages, addresses, routes and delivers data over a networks. Throughout this video based training video, you use various network tools to capture and dissect network packets. You will explore, in detail, the IP (Internet Protocol), ICMP, TCP, UDP, and how they all interact together. You will explore how TCP/IP works through the Session and Application layers of the OSI model. Wireless network fundamentals is also covered, with tips on protecting your data with WEP and WPA. Finally, Ric breaks down what IPv6 is, and why it is important. This course is designed to be a beginners course on the theory and hands on analysis of TCP/IP. By the time you have completed this course, you will have a thorough understanding of what a packet is and how it delivers data from point to point using TCP/IP.